Sarcoptic mange in a guanaco (Lama guanicoe) of northwestern Argentina : Clinical, histopathological and molecular studies - Sosa, Fabiana Evangelina; Anello, Melina; Ferreyra, Hebe del Valle; Medina Vallejo, Diego M.; Micheloud, Juan Francisco; Borsetti, Hugo M.; Hernández, Nancy; Florin-Christensen, Monica; Romero, Sandra Raquel (Elsevier, 2025)
Sarcoptic mange, caused by the mite Sarcoptes scabiei, is a highly contagious and potentially fatal skin disease that affects a wide range of mammals, including South American Camelids (SAC). Although the presence of mange has been described in vicuñas and llamas in northwestern Argentina, there are no previous records documenting its presence in guanacos (Lama guanicoe) of this region. We here describe a case of S. scabiei in a free-ranging guanaco in the Department of Tilcara, Jujuy Province. The animal presented alopecic, erythematous and hyperkeratotic lesions with abundant crusts in the ventral region of the body and limbs. Histopathology revealed periadnexal dermatitis with inflammatory infiltrate, severe hyperemia, orthokeratotic and parakeratotic epidermal hyperplasia, and stratum corneum thickening. The etiological agent was identified as S. scabiei by microscopic examination of adult mites. This result was confirmed by sequencing of a cytochrome oxidase subunit I gene fragment, that showed 100 % identity with sequences of isolates from SAC and other mammals. Genotyping of three mites isolated from different parts of the guanaco's body using a set of ten microsatellite markers indicated the infection with a single genetic variant that showed a similar profile to those found in S. scabiei isolates from vicuñas and llamas of the same region. However, genetic differences with guanaco isolates from midwestern Argentina were observed. This work presents the first record of sarcoptic mange in a guanaco in Jujuy Province and in the northwestern region of Argentina, as well as the molecular characterization of the etiological agent. The case highlights an uncertain scenario regarding the health situation of the guanaco population in this region, which is small, fragmented, and locally categorized as endangered. Epidemiological surveillance programs for guanacos and further research on the impact of sarcoptic mange on the conservation of this species are needed.